Medida do volume pulmonar fetal por US 3D como marcador de letalidade em fetos com displasias ósseas - Carolina Amorim de Barros (2013)
Objective: to study the capacity of three-dimensional ultrasound (3D US) in predicting lethality in fetuses with skeletal dysplasia. Methods: 24 fetuses were studied and bilateral lung scans were performed during one ultrasound session, three times in each fetus. The samples of 3D ultrasound fetal chest volume were acquired preferably when the fetus was facing towards the transducer and was not moving. The VOCAL method was used to obtain a sequence of six sections of each lung around a fixed axis and a rotation angle of 30o was adopted. The lung volume measurements were analyzed according to normogram. After birth, lung hypoplasia was diagnosed considering clinical and radiological criteria. In this study we did not have access to pathologic criteria. Results: 18 (75%) of all cases of skeletal dysplasia were lethal. From the lethal cases, after post natal diagnosis, 4 were osteogenesis imperfecta type II, 3 were thanatoforic dysplasia, 2 were campomelic dysplasia. The other 9 remained without a final diagnosis. The accuracy of 3D US in predicting lethality in fetuses with skeletal dysplasia was high, with a sensibility of 83.3%, specificity of 100%, positive predictive value of 100% and negative predictive value of 66.7%. Compared to bidimensional methods used for predicting lethality (TC, TC/CA, TA/CA), 3D US had a better overall accuracy. Through the Kappa index of 0.174 it was possible to say that there was a substantial agreement between the possibility of lethality when the 3D ultrasound measurement was altered and real lethality after birth. This agreement was statistically significant, since the value of p < 0.001. Conclusion: This study suggests that 3D US is a good predictor of lethal pulmonary hypoplasia in fetuses with skeletal dysplasia, with high accuracy.